PUF pattern with buckling layered structure and preparation method thereof

By adopting PUF patterns with buckling layered structure and their preparation method in the anti-counterfeiting label, the problems of cumbersome preparation process, high material cost and susceptibility to environmental interference in the prior art are solved, and high stability of low-cost and simple processes are achieved Anti-counterfeiting patterns with uniqueness and recognizability.

CN119416808AActive Publication Date: 2025-02-11NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411485272.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The preparation process of existing anti-counterfeiting labels is cumbersome, the material cost is high, and it is easily disturbed by external environment, affecting the anti-counterfeiting effect.

Method used

Using PUF pattern with buckling layered structure and its preparation method, the plasma treatment and ultraviolet cross-linking are performed by spin-coating PDMS and PVA aqueous solution, and the aqueous ethanol solution is added dropwise to form a stable PVA/PDMS double-layer film, and finally spin-coating PDMS To enhance the stability of the pattern.

Benefits of technology

It has achieved a PUF pattern with low production cost, simple process, stability, uniqueness, recognizability and physically uncloned PUF pattern, which can be practically applied in the field of anti-counterfeiting and has huge market value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119416808A_ABST
    Figure CN119416808A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-counterfeit labels, and discloses a PUF pattern with a buckling layered structure and a preparation method of the PUF pattern. The preparation method comprises the following steps: spin-coating PDMS on a substrate, heating and curing, carrying out plasma treatment to obtain a PDMS film, further spin-coating a PVA aqueous solution containing NaB on the PDMS film, drying, carrying out ultraviolet crosslinking to obtain a PVA / PDMS double-layer film, dropwise adding an ethanol aqueous solution under specific heat treatment conditions, and spin-coating PDMS for pattern protection to obtain a PUF pattern which has a buckling layered structure, and has the characteristics of high strength, good mechanical properties, good mechanical properties and the like. The layered structure is a completely self-assembled process and has the characteristics of uniqueness, randomness, identifiability, physical unclonability and high stability. The preparation method provided by the invention has the advantages of simple process, easily available raw materials and lower cost, can be practically applied in the anti-counterfeiting field, and has huge market value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-counterfeiting labels, and in particular to a PUF pattern with a buckled layered structure and a preparation method thereof. Background Art

[0002] Counterfeit goods have a significant impact on economic development. Integrating anti-counterfeiting labels with PUF (unclonable function) into goods is a promising solution. Some patterns generated by surface instability have PUF characteristics. On the one hand, they can be made into labels by random processes and become "keys". On the other hand, the patterns generated by instability can be stored and become "locks". The combination of the two can achieve strong anti-counterfeiting. Surface instability is a phenomenon in which the internal balance of the system is broken under the stimulation of the physical field, resulting in changes in the surface morphology, such as wrinkles, buckling and delamination.

[0003] Most of the existing anti-counterfeiting patterns on labels are made of special optical materials, and the preparation of existing anti-counterfeiting labels also requires high-precision technology and equipment support, such as laser confocal imaging, layer-by-layer scanning, etc. However, there are many problems in the selection and preparation of materials for existing anti-counterfeiting patterns on labels, such as: optical materials are not only expensive, but also may have unstable optical material structures, thus affecting the anti-counterfeiting effect; the preparation process of existing anti-counterfeiting labels is not only cumbersome, but also the anti-counterfeiting labels prepared by existing processes are easily disturbed by the external environment, thus affecting the anti-counterfeiting effect. Therefore, it is of great significance to provide a PUF pattern and its preparation method with low production cost, simple process, randomness, good recognizability and stability. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a PUF pattern with a buckled layered structure and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention provides a method for preparing a PUF pattern with a buckled layered structure, comprising the following steps:

[0006] S1, spin coating PDMS onto a substrate, curing at 80°C-120°C, and then performing surface modification by plasma treatment to obtain a PDMS film;

[0007] S2, spin coating a PVA aqueous solution containing NaB on the PDMS film, drying at 40° C.-60° C., and then UV cross-linking to obtain a PVA / PDMS double-layer film;

[0008] S3, preheating the PVA / PDMS double-layer film at 30° C.-60° C., then dropping an ethanol aqueous solution, and drying to obtain a primary PUF pattern;

[0009] S4, spin coating PDMS on the primary PUF pattern to obtain the PUF pattern.

[0010] Compared with the prior art, the PUF pattern provided by the present invention is obtained by simply preparing a double-layer film and using droplets to induce the surface to buckle and delaminate; after dropping an ethanol aqueous solution on the PVA / PDMS double-layer film, the PVA film in the PVA / PDMS double-layer film swells by absorbing water to generate an interfacial stress σ between the double-layer films. Due to the large modulus of the PDMS film, the critical stress σ for the occurrence of wrinkling instability is c becomes larger, and when it exceeds the interface stress σ between the double-layer membranes, wrinkle instability will not occur; however, since the interface stress σ cannot be released through wrinkle instability, and when the local interface stress exceeds the bonding strength between the double-layer membranes, the PVA film in the PVA / PDMS double-layer membrane will undergo irreversible delamination to release the interface stress. Due to the mismatch of the interface stress, a PUF pattern with a buckled layered structure is formed, which has the characteristics of strong stability, uniqueness, identifiability, randomness and physical non-cloning. Further, the present invention can further enhance the stability and heat resistance and waterproofness of the PUF pattern by spin coating PDMS on the primary PUF pattern. The PUF pattern prepared by the preparation method provided by the present invention has a buckled layered structure, and this layered structure is a completely autonomous assembly process, which has the characteristics of uniqueness, randomness, identifiability, physical non-cloning and strong stability. The preparation method provided by the present invention has a simple process, easy-to-obtain raw materials, low cost, can be practically applied in the field of anti-counterfeiting, and has great market value.

[0011] Preferably, in S1, the substrate is a hard substrate, which may be glass, polymethyl methacrylate or polyethylene terephthalate, and is ultrasonically cleaned and dried with anhydrous ethanol and deionized water before use. The substrate of the present invention has no special requirements on thickness, as long as it can achieve the supporting function.

[0012] Preferably, in S1, the curing ratio of the PDMS is (15-30):1.

[0013] It should be explained that the curing ratio refers to the mass ratio of the main agent to the curing agent.

[0014] Preferably, the model of the PDMS main agent in the PDMS is C-105, and the model of the curing agent is C-105.

[0015] Preferably, in S1, the amount of PDMS is (0.8 g-1.2 g) / 9 cm 2 .

[0016] Preferably, in S1, the spin coating rate is 300 rpm-700 rpm.

[0017] Preferably, in S1, the spin coating time is 30s-90s.

[0018] Preferably, in S1, the curing time is 45s-60s.

[0019] Preferably, in S1, the power of the plasma treatment is 50W-55W.

[0020] Preferably, in S1, the plasma treatment time is 45s-60s.

[0021] By further limiting the power and time of plasma treatment, the hydrophilicity of the PDMS surface can be further enhanced, making it easier for the PVA aqueous solution to spread onto the PDMS surface, improving the affinity of the interface, and thus further improving the stability of the PUF pattern.

[0022] Preferably, in S2, the concentration of the PVA aqueous solution is (150 mg-250 mg) / mL.

[0023] Preferably, in S2, the mass ratio of NaB to PVA in the PVA aqueous solution is (0.02-0.1):1.

[0024] Preferably, in S2, the spin coating rate is 800 rpm-1200 rpm.

[0025] Preferably, in S2, the spin coating time is 30s-90s.

[0026] Preferably, in S2, the amount of the PVA aqueous solution containing NaB is (0.8 g-1.2 g) / 9 cm 2 .

[0027] Preferably, in S2, the drying time is 1 h-2 h.

[0028] Preferably, in S2, the conditions for the UV crosslinking are: the wavelength of the UV light is 254 nm, the energy density is 5 mW / cm 2 .

[0029] Preferably, in S2, the UV cross-linking time is 1.5h-3h.

[0030] Preferably, in S3, the preheating time is 1 min-2 min.

[0031] Preferably, in S3, the volume ratio of water to ethanol in the ethanol aqueous solution is 1:9-4:6.

[0032] Preferably, in S3, the amount of the ethanol aqueous solution is (4.8 μL-5.2 μL) / cm 2 .

[0033] By limiting the volume ratio of water and ethanol in the ethanol-water solution and the amount of the ethanol-water solution, a specific interfacial stress difference can be formed between the PVA film and the PDMS film in the PVA / PDMS double-layer film, so that the obtained PUF pattern has a distinct buckled layered structure, obvious identifiable features, and the characteristic of being physically unclonable.

[0034] Preferably, in S4, the curing ratio of the PDMS is (15-30):1.

[0035] Further preferably, the model of the PDMS main agent in the PDMS is C-105, and the model of the curing agent is C-105.

[0036] Preferably, in S4, the amount of PDMS is (0.8 g-1.2 g) / 9 cm 2 .

[0037] Preferably, in S4, the spin coating rate is 300 rpm-700 rpm.

[0038] Preferably, in S4, the spin coating time is 30s-90s.

[0039] The present invention also provides a PUF pattern with a buckled layered structure, which is prepared by the above-mentioned method for preparing the PUF pattern with a buckled layered structure.

[0040] The present invention spin-coats PDMS on a substrate, heats and solidifies it, and then treats it with plasma to obtain a PDMS film. The PDMS film is further spin-coated with a PVA aqueous solution containing NaB, and then dried and UV-crosslinked to obtain a PVA / PDMS double-layer film. An ethanol aqueous solution is added dropwise under specific heat treatment conditions, and then PDMS is spin-coated for pattern protection to obtain a PUF pattern having a buckled hierarchical structure. This hierarchical structure is a completely autonomous assembly process, and has the characteristics of uniqueness, randomness, recognizability, physical non-cloning, and strong stability. The preparation method provided by the present invention has a simple process, readily available raw materials, and low cost. It can be practically applied in the field of anti-counterfeiting and has great market value. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0042] Figure 1 This is a micrograph of a PUF pattern with a buckled layered structure prepared in Example 1 of the present invention;

[0043] Figure 2 A micrograph of a PUF pattern with a buckled layered structure prepared in Example 2 of the present invention;

[0044] Figure 3 A micrograph of a PUF pattern with a buckled layered structure prepared in Example 3 of the present invention;

[0045] Figure 4 This is a micrograph of the PUF pattern with a buckled layered structure prepared in Example 1 of the present invention after being placed in an oven at 150° C. for 2 hours;

[0046] Figure 5 Micrographs of the PUF pattern with a buckled layered structure prepared in Example 1 of the present invention after being subjected to water dripping and water immersion treatments;

[0047] Figure 6 A micrograph of a pattern prepared in Comparative Example 1 of the present invention;

[0048] Figure 7 A micrograph of a pattern prepared in Comparative Example 2 of the present invention;

[0049] Figure 8 This is a micrograph of the pattern prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0050] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0051] Example 1

[0052] This embodiment provides a method for preparing a PUF pattern with a buckled layered structure, comprising the following steps:

[0053] S1. Spin-coat PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 15:1 onto a 1 cm thick substrate at a rate of 300 rpm for 30 seconds, then cure at 120°C for 45 seconds, and perform surface modification by plasma treatment to obtain a PDMS film; wherein, the amount of PDMS relative to the substrate area is 0.8 g / 9 cm 2 , the power of plasma treatment is 50W, and the time of plasma treatment is 60s;

[0054] S2, spin coating a PVA aqueous solution containing NaB on the PDMS film at a rate of 800 rpm for 90 seconds, drying at 60°C for 1 hour, and then UV crosslinking for 1.5 hours to obtain a PVA / PDMS double-layer film; wherein the concentration of the PVA aqueous solution is 250 mg / mL, the mass ratio of NaB to PVA in the PVA aqueous solution is 0.1:1, and the amount of the PVA aqueous solution containing NaB relative to the substrate area is 0.8 g / 9 cm 2 The conditions for UV crosslinking are: the wavelength of UV light is 254nm and the energy density is 5mW / cm 2 ;

[0055] S3, preheating the PVA / PDMS double-layer film at 60°C for 1 min, then dripping ethanol aqueous solution and drying to obtain a primary PUF pattern; wherein the volume ratio of water to ethanol in the ethanol aqueous solution is 1:9, and the amount of ethanol aqueous solution relative to the substrate area is 4.8 μL / cm 2 ;

[0056] S4, spin coating PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 15:1 on the primary PUF pattern at a rate of 300 rpm for 90 seconds to obtain the PUF pattern; wherein the amount of PDMS relative to the substrate area is 0.8 g / 9 cm 2 .

[0057] Example 2

[0058] This embodiment provides a method for preparing a PUF pattern with a buckled layered structure, comprising the following steps:

[0059] S1. Spin-coat PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 30:1 onto a 1 cm thick substrate at a rate of 700 rpm for 90 seconds, then cure at 80°C for 60 seconds, and perform surface modification by plasma treatment to obtain a PDMS film; wherein, the amount of PDMS relative to the substrate area is 1.2 g / 9 cm 2 , the power of plasma treatment is 55W, and the time of plasma treatment is 45s;

[0060] S2, spin coating a PVA aqueous solution containing NaB on the PDMS film at a rate of 1200 rpm for 30 seconds, drying at 40°C for 2 hours, and then UV crosslinking for 3 hours to obtain a PVA / PDMS double-layer film; wherein the concentration of the PVA aqueous solution is 150 mg / mL, the mass ratio of NaB to PVA in the PVA aqueous solution is 0.02:1, and the amount of the PVA aqueous solution containing NaB relative to the substrate area is 1.2 g / 9 cm 2The conditions for UV crosslinking are: the wavelength of UV light is 254nm and the energy density is 5mW / cm 2 ;

[0061] S3, preheating the PVA / PDMS double-layer film at 30°C for 2 minutes, then dripping ethanol aqueous solution and drying to obtain a primary PUF pattern; wherein the volume ratio of water to ethanol in the ethanol aqueous solution is 1:4, and the amount of ethanol aqueous solution relative to the substrate area is 5.2 μL / cm 2 ;

[0062] S4, spin-coating PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 30:1 on the primary PUF pattern at a rate of 700 rpm for 30 seconds to obtain the PUF pattern; wherein the amount of PDMS relative to the substrate area is 1.2 g / 9 cm 2 .

[0063] Example 3

[0064] This embodiment provides a method for preparing a PUF pattern with a buckled layered structure, comprising the following steps:

[0065] S1. Spin-coat PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 20:1 onto a 1 cm thick substrate at a rate of 500 rpm for 60 seconds, then cure at 100°C for 50 seconds, and perform surface modification by plasma treatment to obtain a PDMS film; wherein, the amount of PDMS relative to the substrate area is 1 g / 9 cm 2 , the power of plasma treatment is 53W, and the time of plasma treatment is 50s;

[0066] S2, spin coating a PVA aqueous solution containing NaB on the PDMS film at a rate of 1000 rpm for 60 seconds, drying at 50°C for 1.5 hours, and then UV crosslinking for 2 hours to obtain a PVA / PDMS double-layer film; wherein the concentration of the PVA aqueous solution is 200 mg / mL, the mass ratio of NaB to PVA in the PVA aqueous solution is 0.06:1, and the amount of the PVA aqueous solution containing NaB relative to the substrate area is 1 g / 9 cm 2 The conditions for UV crosslinking are: the wavelength of UV light is 254nm and the energy density is 5mW / cm 2 ;

[0067] S3, preheating the PVA / PDMS double-layer film at 50°C for 1.5 min, then dripping ethanol aqueous solution and drying to obtain a primary PUF pattern; wherein the volume ratio of water to ethanol in the ethanol aqueous solution is 1:9, and the amount of ethanol aqueous solution relative to the substrate area is 5 μL / cm2 ;

[0068] S4, spin coating PDMS (the model of PDMS main agent is C-105, and the model of curing agent is C-105) with a curing ratio of 20:1 on the primary PUF pattern at a rate of 400 rpm for 40 seconds to obtain the PUF pattern; wherein the amount of PDMS relative to the substrate area is 1 g / 9 cm 2 .

[0069] Comparative Example 1

[0070] This comparative example provides a pattern, which is different from Example 1 in that: in S3, the dripping of ethanol aqueous solution is replaced by spraying water;

[0071] The other ingredients and preparation process are the same as those in Example 1.

[0072] Comparative Example 2

[0073] This comparative example provides a pattern, which is different from Example 1 in that: in S3, the volume ratio of water to ethanol in the ethanol aqueous solution is 6:4;

[0074] The other ingredients and preparation process are the same as those in Example 1.

[0075] Comparative Example 3

[0076] This comparative example provides a pattern, which is different from Example 1 in that: in S3, the volume ratio of water to ethanol in the ethanol aqueous solution is 8:2;

[0077] The other ingredients and preparation process are the same as those in Example 1.

[0078] Depend on Figure 1-3 It can be seen that the PUF pattern prepared by the method provided by the present invention has a buckled layered structure, which has obvious bifurcation points and breakpoints and has obvious identifiability;

[0079] The present invention repeats the operation of Example 1 to prepare a PUF pattern and Figure 1 Obviously different, see Figure 4 The picture before processing also has obvious bifurcation points and breakpoints, which also proves that the PUF pattern prepared by the method provided by the present invention has uniqueness, randomness and identifiability. After placing it in an oven at 150°C for 2 hours, microscopic observation shows that the pattern does not change after heating, which also proves that the PUF pattern prepared by the method provided by the present invention has heat-resistant stability;

[0080] Figure 5 The PUF pattern is prepared by the method of Example 1 of the present invention. Since the PUF prepared by the preparation method is random and identifiable, the prepared pattern and Figure 1Different, but also have obvious bifurcation points and breakpoints. After dripping and immersing in water for 5 minutes, the pattern after treatment does not change, which also proves that the PUF pattern prepared by the method provided by the present invention has water resistance and stability;

[0081] Depend on Figure 6 It can be seen that when the dripping of ethanol water solution is changed to spraying water, although the prepared pattern also has bifurcation points and breakpoints, there is no obvious buckling layered structure, and its bifurcation points and breakpoints overlap seriously, making it difficult to identify;

[0082] Depend on Figure 7 and 8 It can be seen that after adjusting the volume ratio of water and ethanol in the ethanol-water solution, the prepared pattern has no obvious buckling layered structure and has very few bifurcation points and breakpoints, and the identifiable features are not obvious.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PUF pattern with a buckled layered structure, characterized in that: The steps include: S1, spin coating PDMS onto a substrate, curing at 80°C-120°C, and then performing surface modification by plasma treatment to obtain a PDMS film; S2, spin coating a PVA aqueous solution containing NaB on the PDMS film, drying at 40° C.-60° C., and then UV cross-linking to obtain a PVA / PDMS double-layer film; S3, preheating the PVA / PDMS double-layer film at 30° C.-60° C., then dropping an ethanol aqueous solution, and drying to obtain a primary PUF pattern; S4, spin coating PDMS on the primary PUF pattern to obtain the PUF pattern.

2. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S1, the curing ratio of the PDMS is (15-30):1; and / or In S1, the amount of PDMS is (0.8g-1.2g) / 9cm 2 ; and / or In S1, the spin coating rate is 300 rpm-700 rpm; and / or In S1, the spin coating time is 30s-90s; and / or In S1, the curing time is 45s-60s.

3. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S1, the power of the plasma treatment is 50W-55W; and / or In S1, the plasma treatment time is 45s-60s.

4. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S2, the concentration of the PVA aqueous solution is (150 mg-250 mg) / mL; and / or In S2, the mass ratio of NaB to PVA in the PVA aqueous solution is (0.02-0.1):1; and / or In S2, the spin coating rate is 800 rpm-1200 rpm; and / or In S2, the spin coating time is 30s-90s.

5. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S2, the amount of the PVA aqueous solution containing NaB is (0.8g-1.2g) / 9cm 2 ; and / or In S2, the drying time is 1h-2h; and / or In S2, the conditions for the UV crosslinking are: the wavelength of the UV light is 254 nm, and the energy density is 5 mW / cm 2 ; and / or In S2, the UV cross-linking time is 1.5h-3h.

6. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S3, the preheating time is 1 min-2 min.

7. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S3, the volume ratio of water to ethanol in the ethanol aqueous solution is 1:9-4:6; and / or In S3, the amount of the ethanol aqueous solution is (4.8 μL-5.2 μL) / cm 2 . .

8. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S4, the curing ratio of the PDMS is (15-30):1; and / or In S4, the amount of PDMS is (0.8g-1.2g) / 9cm 2 .

9. The method for preparing a PUF pattern with a buckled layered structure according to claim 1, characterized in that: In S4, the spin coating rate is 300 rpm-700 rpm; and / or In S4, the spin coating time is 30s-90s.

10. A PUF pattern with a buckled layered structure, characterized in that: The PUF pattern having a buckled layered structure is prepared by the method for preparing the PUF pattern having a buckled layered structure according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Manufacturing method and application of PUF (Physical Unclonable Function) pattern and anti-counterfeit label

    CN114973911A

  • Method of forming buckling of thin films and a element using the thin films

    KR1020150021606A

  • 3D Anti-counterfeiting pattern and processing of the same

    US20220410607A1

Cited By

  • Fluorescent wrinkle anti-counterfeiting identification label and preparation method thereof

    CN119942904A